I-STEM-PBL: Framework on biology education for sustainable development - Funa, Aaron A. (Animo Repository, 2023)
The United Nations Educational, Scientific, and Cultural Organization is urging the scaling up of sustainable development (SD) interventions in education. To address this, I explored a framework for biology education that combines Integrated Science, Technology, Engineering, and Mathematics with Problem-Based Learning, termed I-STEM-PBL. The aim was to improve instruction and meet evolving educational needs while evaluating my own teaching practices. The study was contextualized in reigniting youth interest in Pili (Canarium ovatum), an endemic product in Sorsogon, where I taught. Employing a practitioner inquiry approach, I applied the Plan, Do, Study, and Act model. A mixed methods design collected quantitative data (N = 38) and qualitative data (n = 20) at a public secondary school in Sorsogon, Bicol, Philippines, renowned for Pili production. The findings highlighted positive feedback from students, indicating action-orientation, learner-centeredness, and transformative learning. Throughout the I-STEM-PBL process, students demonstrated conceptual learning and scientific creativity. The evaluation revealed the module's effectiveness in improving students' understanding of biomolecules and their behaviors towards SD, as well as their perceptions of active learning. However, as a teacher-researcher, I faced challenges alongside the students, including time and resource limitations. These challenges were mitigated through the implementation of differentiated instruction and an emphasis on communication and collaboration. Insights emphasized the importance of guidance, active engagement, and a supportive learning environment. The study's limitations included a small sample size and location-specific findings, emphasizing the need for replication with larger and more diverse samples. Recommendations include integrating the I-STEM-PBL into the curriculum, providing professional development programs for teachers to ensure effective implementation, and enhancing the framework to strike a balance between the objectives of SD and the curriculum standards set by the DepEd. Keywords: Education for sustainable development, problem-based learning, STEM education, sustainable development